Strategi Guru Dalam Mengatasi Kesulitan Membaca Pada Siswa Kelas II SD Negeri 107399 Bandar Khalifah - Riris Nur Kholida Rambe; Devita Aulia Putri; Nurul Hasanah; Sri Ramahyanti Berutu; Winda Amelia Putri; Zahra Azzura Jaffa (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze reading difficulties in class ll students at SD Negeri 1-7399 Bandar Khalifah and find out the strategies of class ll teacher at SD Negeri 107399 Bandar Khalifah. This type of research uses descriptive qualitative research mothods. The qualitative method is a research method that focuses on in depth observations of the object of research. The subject of this research of this research at SD Negeri 107399 Bandar Khalifah named Mrs. Yustika. In addition, the method of data collection was by interviewing Mrs Yustika at Sd Negeri 107399 Bandar Khalifah. The result showed that students reading difficulties were caused by: 1) Difficulty in recognizing letters, 2) Spelling letters, 3) Lack of understanding of the contents if the reading so that it makes them stammer. The classroom teacher strategy used is: 1) By routinely practicing reading every day and being listened to by the teacher, 2) Give students a reading assignment at home for at least 5 minutes and then repeat ut again at school, 3) Do random guessing games so students will recognize these letters better, 4. Proovide motivation continuously to students, inviliting students to learn to read while playing for example playing word cards and choosing books whose words are easy for students to understand.